Conductive paste, electronic components, and multilayer ceramic capacitors
The conductive paste, featuring an additive that enhances adhesion, addresses the issue of insufficient adhesion between the dry film and substrate in multilayer ceramic capacitors, particularly when pressing time and pressure are reduced, thereby improving manufacturing yield.
Patent Information
- Application Number
- JP2024512630
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-28
- Filing Date
- 2023-03-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-03-28
AI Technical Summary
Conductive pastes used in the manufacturing of multilayer ceramic capacitors do not provide sufficient adhesion between the dry film and the substrate when the pressing time and pressure during the heating and pressing process are reduced, leading to misalignment and decreased yield.
A conductive paste is developed containing a conductive powder, an additive with a specific structural formula, a binder resin, and an organic solvent. The additive enhances adhesion by inhibiting resin interaction, allowing the dry film to soften and improve adhesion to the ceramic green sheet.
The conductive paste significantly improves adhesion between the dry film and the substrate, reducing misalignment and increasing yield, even under reduced pressing time and pressure conditions.
Smart Images

Figure 0007648002000016 
Figure 0007648002000001 
Figure 0007648002000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive paste, an electronic component, and a multilayer ceramic capacitor. [Background technology]
[0002] As electronic devices such as mobile phones and digital devices become smaller and more powerful, there is a demand for smaller electronic components, including multilayer ceramic capacitors, with higher capacitance. Multilayer ceramic capacitors have a structure in which a plurality of dielectric layers and a plurality of internal electrode layers are alternately laminated, and by making these dielectric layers and internal electrode layers thinner, it is possible to achieve smaller size and higher capacitance.
[0003] For example, a multilayer ceramic capacitor is manufactured as follows. First, a conductive paste for internal electrodes is printed in a predetermined electrode pattern on the surface of a green sheet containing a dielectric powder such as barium titanate (BaTiO3) and a binder resin, and then dried to form a dry film (conductive film). Next, the dry film and the green sheet are alternately laminated to obtain a laminate. Next, this laminate is integrated by heat and pressure bonding to form a pressure-bonded body. This pressure-bonded body is cut, and an organic binder removal process is performed in an oxidizing atmosphere or an inert atmosphere, and then sintered to obtain a sintered chip. Next, a paste for external electrodes is applied to both ends of the sintered chip, and after sintering, nickel plating or the like is performed on the surface of the external electrodes to obtain a multilayer ceramic capacitor.
[0004] In the process of thermocompression bonding and cutting the laminate formed by stacking the dry film and the green sheet, if the adhesion between the dry film and the green sheet (substrate) is insufficient, the dry film (conductive film) may peel off from the green sheet (substrate) or the layer structure may become misaligned, and the resulting multilayer ceramic capacitor may not have the desired electrical characteristics.
[0005] For example, Patent Document 1 discloses a conductive paste containing a (meth)acrylic resin as a binder resin, an organic solvent, and a metal powder, with the aim of improving the adhesion of the conductive paste containing a (meth)acrylic resin as a binder resin to a ceramic green sheet, wherein the (meth)acrylic resin has a glass transition temperature Tg in the range of -60°C to 120°C, a hydroxyl group in the molecule in the range of 0.01% by mass to 5% by mass, an acid value in the range of 1 mgKOH / g to 50 mgKOH / g, and a weight average molecular weight in the range of 10,000 Mv to 350,000 Mv.
[0006] Furthermore, Patent Document 2 discloses a conductive paste for forming an electrode layer on a substrate, with the aim of providing a conductive paste capable of forming a conductive film having excellent adhesion to the substrate, the conductive paste comprising a conductive powder, a resin binder, an organic additive, and an organic solvent, wherein the organic additive comprises a (meth)acrylate compound having two or more (meth)acryloyl groups in one molecule and having a number average molecular weight of 1,000 or less.
[0007] Furthermore, Patent Document 3 discloses a dry film for an internal electrode of a multilayer ceramic capacitor, which is formed from a composition containing a conductive powder and an organic binder resin, for the purpose of providing a dry film for an internal electrode that is excellent in adhesion to a dielectric layer and that is capable of forming an internal electrode whose shape does not change significantly before and after heat treatment, and which is characterized in that the dry film for an internal electrode of a multilayer ceramic capacitor has a Vickers hardness of 47 Hv or more and 51 Hv or less. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2013 / 187183 [Patent Document 2] JP 2018-055933 A [Patent Document 3] JP 2019-121744 A Summary of the Invention [Problem to be solved by the invention]
[0009] In recent years, from the viewpoint of improving productivity and reducing costs, in the manufacturing process of multilayer ceramic capacitors, the pressing time and pressure during heating and pressing of a laminate obtained by alternately stacking dry films and ceramic green sheets are sometimes shortened.
[0010] However, when the pressing time or pressure during compression is reduced, the conventional conductive paste does not provide sufficient adhesion between the dry film and the substrate, which may cause the dry film to shift in position and reduce the yield. Therefore, there is a demand for a conductive paste that can further improve the adhesion to the substrate when the dry film is formed.
[0011] In view of the above circumstances, an object of the present invention is to provide a conductive paste that can further improve adhesion to a substrate. [Means for solving the problem]
[0012] In a first aspect of the present invention, there is provided a conductive paste comprising a conductive powder, an additive, a binder resin and an organic solvent, the conductive paste comprising, as the additive, a compound having a structural portion represented by the following formula (1):
[0013] [ka]
[0014] In the above formula (1), R 1 represents a saturated or unsaturated aliphatic hydrocarbon group having 8 to 25 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH-) substituted with oxygen (-O-); R 2represents hydrogen or a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and one or more methylenes (-CH2-) in the aliphatic hydrocarbon group may be substituted with oxygen (-O-).
[0015] Moreover, the compound preferably has a structure represented by the following formula (2) or (3).
[0016] [ka]
[0017] [ka]
[0018] In the above formulas (2) and (3), R 1 , R 5 each independently represents a saturated or unsaturated aliphatic hydrocarbon group having 8 to 25 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH-) substituted with oxygen (-O-), R 2 , R 3 , R 4 each independently represents hydrogen or a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH-) substituted with oxygen (-O-), R 6 represents a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH2-) substituted with oxygen (-O-).
[0019] The compound is preferably contained in an amount of 0.01% by mass or more and 2.0% by mass or less with respect to the entire conductive paste. The compound is preferably contained at a temperature of 200° C. or more at which the weight loss rate is maximized in thermogravimetric analysis. The compound is preferably contained in an amount of 250 to 3000 by mass. The conductive paste preferably further contains an acid dispersant and / or a base dispersant. The conductive powder is preferably contained at least one metal powder selected from Ni, Pd, Pt, Au, Ag, Cu, and alloys thereof. The conductive powder is preferably contained in an average particle size of 0.05 μm to 1.0 μm. The binder resin is preferably contained in a butyral resin. The conductive paste preferably further contains a ceramic powder. The ceramic powder is preferably contained in a barium titanate. The ceramic powder is preferably contained in an average particle size of 0.01 μm to 0.5 μm. The ceramic powder is preferably contained in an amount of 1% by mass or more and 20% by mass or less with respect to the entire conductive paste. The conductive paste is preferably for use in internal electrodes of multilayer ceramic components.
[0020] In a second aspect of the present invention, there is provided an electronic component formed using the above-mentioned conductive paste.
[0021] In a third aspect of the present invention, there is provided a multilayer ceramic capacitor having at least a laminate in which dielectric layers and internal electrode layers are laminated, the internal electrode layers being formed using the above-mentioned conductive paste. Effect of the Invention
[0022] The conductive paste of the present invention can further improve adhesion to a substrate, and in the manufacturing process of a multilayer ceramic capacitor, a dried film (internal electrode layer) formed using the conductive paste of the present invention has high adhesion to a green sheet (dielectric layer). [Brief description of the drawings]
[0023] [Figure 1]FIG. 1 is a perspective view and a cross-sectional view showing a multilayer ceramic capacitor according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] [Conductive paste] The conductive paste of the present embodiment contains a conductive powder, a ceramic powder, a dispersant, a binder resin, and an organic solvent. Each component will be described in detail below.
[0025] (conductive powder) The conductive powder is not particularly limited, and metal powder can be used, for example, powder of one or more selected from Ni, Pd, Pt, Au, Ag, Cu, and alloys thereof. Among these, from the viewpoints of conductivity, corrosion resistance, and cost, powder of Ni or its alloy (hereinafter, sometimes referred to as "Ni powder") is preferable. As the Ni alloy, for example, an alloy of Ni and at least one element selected from the group consisting of Mn, Cr, Co, Al, Fe, Cu, Zn, Ag, Au, Pt, and Pd can be used. The Ni content in the Ni alloy is, for example, 50 mass% or more, preferably 80 mass% or more. In addition, the Ni powder may contain about several hundred ppm of element S in order to suppress sudden gas generation due to partial thermal decomposition of the binder resin during the binder removal process.
[0026] The average particle size of the conductive powder is preferably 0.05 μm or more and 1.0 μm or less, more preferably 0.1 μm or more and 0.5 μm or less. When the average particle size of the conductive powder is within the above range, it can be suitably used as an internal electrode paste for a thin-film multilayer ceramic capacitor (multilayer ceramic component). The average particle size is a value determined by observation with a scanning electron microscope (SEM), and is the average value (SEM average particle size) obtained by measuring the particle size of each of a plurality of particles from an image observed with an SEM at a magnification of 10,000 times.
[0027] The content of the conductive powder is preferably 30% by mass or more and less than 70% by mass, more preferably 40% by mass or more and 60% by mass or less, based on the total amount of the conductive paste. When the content of the conductive powder is within the above range, the conductive paste has excellent conductivity and dispersibility.
[0028] (ceramic powder) The ceramic powder is not particularly limited, and for example, in the case of a paste for an internal electrode of a multilayer ceramic capacitor, a known ceramic powder is appropriately selected depending on the type of multilayer ceramic capacitor to be applied. As the ceramic powder, for example, a perovskite oxide containing Ba and Ti can be used, and preferably contains barium titanate (BaTiO3).
[0029] The ceramic powder may be a ceramic powder containing barium titanate as a main component and oxides as sub-components. Examples of oxides include oxides of Mn, Cr, Si, Ca, Ba, Mg, V, W, Ta, Nb, and one or more rare earth elements. The ceramic powder may be a perovskite-type oxide ferroelectric ceramic powder in which the Ba and Ti atoms of barium titanate (BaTiO3) are replaced with other atoms, such as Sn, Pb, and Zr.
[0030] When used as a conductive paste for internal electrodes, the ceramic powder may be powder of the same composition as the dielectric ceramic powder constituting the green sheet of the multilayer ceramic capacitor (electronic component). This suppresses the occurrence of cracks due to a mismatch in shrinkage at the interface between the dielectric layer and the internal electrode layer during the sintering process. In addition to the above, examples of such ceramic powder include oxides such as ZnO, ferrite, PZT, BaO, Al2O3, Bi2O3, R (rare earth element)2O3, TiO2, and Nd2O3. Note that one type of ceramic powder may be used, or two or more types may be used.
[0031] The average particle size of the ceramic powder is, for example, 0.01 μm to 0.5 μm, preferably 0.01 μm to 0.3 μm. When the average particle size of the ceramic powder is in the above range, it is possible to form a sufficiently fine, thin, and uniform internal electrode when used as an internal electrode paste. The average particle size is a value determined by observation with a scanning electron microscope (SEM), and is the average value (SEM average particle size) obtained by measuring the particle size of each of a plurality of particles from an image observed with an SEM at a magnification of 50,000 times.
[0032] The content of the ceramic powder is preferably 1% by mass or more and 20% by mass or less, more preferably 3% by mass or more and 15% by mass or less, based on the total amount of the conductive paste. When the content of the ceramic powder is within the above range, the conductive paste has excellent dispersibility and sinterability.
[0033] The content of the ceramic powder is preferably 1 part by mass or more and 30 parts by mass or less, and more preferably 3 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the conductive powder.
[0034] (binder resin) The binder resin preferably contains a butyral resin. When used as an internal electrode paste, the paste may contain a butyral resin, or may use a butyral resin alone, from the viewpoint of improving the adhesive strength with the green sheet. An example of the butyral resin is polyvinyl butyral (PVB). When the conductive paste contains a butyral resin, the adhesive strength with the green sheet can be further improved.
[0035] The content of the butyral resin may be, for example, 20% by mass or more, 40% by mass or more, or 60% by mass or more, based on the total amount of the binder resin. When the content of the butyral resin is within the above range, the adhesiveness is further improved, and the adhesive strength between the dry film and the green sheet (substrate) is improved.
[0036] The upper limit of the butyral resin content is not particularly limited, but may be, for example, 90% by mass or less, or 80% by mass or less, based on the total binder resin. When the butyral resin content is within the above range, the conductive paste has an appropriate hardness, so that problems such as the printed film not peeling off from the support film and the electrodes being crushed during thermocompression bonding are unlikely to occur.
[0037] The weight average molecular weight (Mw) of the butyral resin may be 30,000 or more and 300,000 or less, 50,000 or more and 200,000 or less, or 100,000 or more and 150,000 or less. The glass transition point Tg of the butyral resin may be 50°C or more and 90°C or less, or 60°C or more and 80°C or less. By including the additive described later in addition to the butyral resin having the above characteristics, a conductive paste with improved adhesion can be obtained. The butyral resin may be used alone or in combination of two or more kinds.
[0038] In addition, a resin other than the butyral resin may be included as a binder resin. The binder resin other than the above is not particularly limited, and a known resin can be used, for example, a cellulose resin such as methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, etc., an acrylic resin, etc. are included. Among them, from the viewpoint of solubility in a solvent, combustion decomposition, etc., it is preferable to include a cellulose resin, and it is more preferable to include ethyl cellulose.
[0039] For example, when a cellulose-based resin is included as a binder resin, the weight average molecular weight (Mw) may be 10,000 to 300,000, 30,000 to 250,000, or 50,000 to 200,000. The hydroxyl value of the cellulose-based resin is not particularly limited, but is preferably 0.1 mgKOH / g to 15 mgKOH / g, more preferably 0.5 mgKOH / g to 7 mgKOH / g, and even more preferably 1.5 mgKOH / g to 3 mgKOH / g. The cellulose-based resin may be included alone or in combination of two or more kinds.
[0040] In addition, when the binder resin contains a cellulose-based resin and a butyral-based resin, from the viewpoint of improving adhesion, the binder resin may contain 20% by mass or more, 40% by mass or more, more than 50% by mass, or 60% by mass or more of the butyral-based resin relative to the total content (100% by mass) of the cellulose-based resin and the butyral-based resin. When the contents of both resins are within the above ranges, the adhesiveness is further improved, and the adhesive strength between the dry film and the green sheet (substrate) may be improved. In addition, the upper limit of the content of the butyral-based resin is not particularly limited, and may be less than 100% by mass, 90% by mass or less, or 80% by mass or less. When the contents of both resins are within the above ranges, the conductive paste can have an appropriate hardness, and defects such as the printed film not peeling off from the support film and the electrode being crushed during thermocompression bonding are less likely to occur.
[0041] The content of the binder resin is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 7% by mass, based on the entire conductive paste. When the content of the binder resin is within the above range, the conductive paste has excellent conductivity and dispersibility.
[0042] The content of the binder resin is preferably 1 part by mass or more and 20 parts by mass or less, and more preferably 1 part by mass or more and 14 parts by mass or less, relative to 100 parts by mass of the conductive powder.
[0043] (Organic solvent) The organic solvent is not particularly limited, and any known organic solvent capable of dissolving the binder resin can be used. Examples of the organic solvent include terpene-based solvents, acetate-based solvents, ether-based solvents, and ketone-based solvents.
[0044] Examples of the terpene solvent include terpineol, dihydroterpineol, and dihydroterpinyl acetate.
[0045] Examples of acetate solvents include isobornyl acetate, isobornyl propionate, isobornyl butyrate, and isobornyl isobutyrate; glycol ether acetates such as ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, dipropylene glycol methyl ether acetate, 3-methoxy-3-methylbutyl acetate, and 1-methoxypropyl-2-acetate; glycol diacetates such as propylene glycol diacetate, 1,4-butanediol diacetate, 1,3-butylene glycol diacetate, and 1,6-hexanediol diacetate; and cyclohexanol acetate.
[0046] Examples of the ether solvent include propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether; ethylene glycol ethers such as diethylene glycol mono-2-ethylhexyl ether, ethylene glycol mono-2-ethylhexyl ether, diethylene glycol monohexyl ether, and ethylene glycol monohexyl ether; dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl-n-butyl ether, and dipropylene glycol dimethyl ether.
[0047] Examples of the ketone solvent include methyl isobutyl ketone, diisobutyl ketone, etc. When a ketone solvent is contained, it is possible to adjust the viscosity without impairing the dispersibility, and it is also possible to improve the drying property.
[0048] The organic solvent preferably contains at least one selected from the group consisting of terpineol, dihydroterpineol, dihydroterpinyl acetate, propylene glycol monobutyl ether, and diethylene glycol monobutyl ether acetate. By containing these organic solvents, the compatibility with the binder resin is excellent and the dispersibility of the filler is excellent.
[0049] The content of the organic solvent (total) is preferably 20% by mass or more and 60% by mass or less, more preferably 25% by mass or more and 45% by mass or less, based on the total amount of the conductive paste. When the content of the organic solvent is in the above range, the conductive paste has excellent conductivity and dispersibility.
[0050] The content of the organic solvent is preferably 50 parts by mass or more and 130 parts by mass or less, more preferably 60 parts by mass or more and 90 parts by mass or less, relative to 100 parts by mass of the conductive powder. When the content of the organic solvent is within the above range, the conductive powder has excellent conductivity and dispersibility.
[0051] The organic solvent may be one type or two or more types. For example, when two or more types of organic solvents are included, at least one selected from the group consisting of terpineol, dihydroterpineol, dihydroterpinyl acetate, propylene glycol monobutyl ether, and diethylene glycol monobutyl ether acetate and a hydrocarbon solvent may be included. In addition to these organic solvents, at least one selected from methyl isobutyl ketone and diisobutyl ketone may be included.
[0052] Examples of the hydrocarbon solvent include solvents containing tridecane, nonane, cyclohexane, etc., mineral spirits, naphthenic solvents, etc. Among them, it is preferable to contain mineral spirits. The content of the hydrocarbon solvent may be 10% by mass or more and 50% by mass or less, or 20% by mass or more and 40% by mass or less, based on the total organic solvent.
[0053] (Additives) (a) Amide compounds The conductive paste according to this embodiment contains, as an additive, a compound having a structural portion represented by the following formula (1) (hereinafter also referred to as an "amide compound").
[0054] [ka]
[0055] In the above formula (1), R 1 represents a saturated or unsaturated aliphatic hydrocarbon group having 8 to 25 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH-) substituted with oxygen (-O-); R 2 represents hydrogen or a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH2-) substituted with oxygen (-O-). The amide compound may not contain an acidic group (e.g., a carboxyl group). If the amide compound contains an acidic group, the softening effect of the dried film may be reduced.
[0056] Moreover, the amide compound preferably has a structure represented by the following structural formula (2) or the following structural formula (3).
[0057] [ka]
[0058] [ka]
[0059] In the above formulas (2) and (3), R 1 , R 5 each independently represents a saturated or unsaturated aliphatic hydrocarbon group having 8 to 25 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH-) substituted with oxygen (-O-), R 2 , R 3 , R 4 each independently represents hydrogen or a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH-) substituted with oxygen (-O-), R 6 represents a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH2-) substituted with oxygen (-O-). 1 ~R 6 The number of carbons in the alkyl group includes the number of methylene (-CH2-) carbons substituted with oxygen (-O-).
[0060] When the conductive paste contains the amide compound, the adhesion of the dry film can be improved. Although the details of the reason are unclear, it is considered that, for example, the amide compound inhibits the interaction between resins, thereby moderately softening the dry film, and the dry film that becomes easily deformed due to the softening, and the resin that does not interact, etc., tend to become entangled at the adhesive interface, thereby improving the adhesion between the dry film and the ceramic green sheet (dielectric layer).
[0061] In the above formulas (1) to (3), R 1 and R 5 The lower limit of the number of carbon atoms in each of R may be independently 8 or more, 12 or more, or 15 or more. 1 and R 5 may have the same number of carbon atoms.
[0062] Also, R 1 and R 5 may have one or more methylene (-CH2-) replaced with oxygen (-O-), or may be an unsubstituted aliphatic hydrocarbon group. 1 and R 5 may have a similar structure.
[0063] In the above formulas (1) to (3), R 2 , R 3 , R 4 The upper limit of the number of carbon atoms in R may be 5 or less, or may be 3 or less. 2 , R 3 , R 4 may be an unsubstituted aliphatic hydrocarbon group, for example, one or more methylenes (-CH2-) may be replaced with oxygen (-O-), or may be hydrogen.
[0064] In the above formula (3), R 6 The upper limit of the number of carbon atoms in R may be 5 or less, 3 or less, or 2 or less. 6 may have one or more methylene (-CH2-) replaced with oxygen (-O-), or may be an unsubstituted saturated hydrocarbon group.
[0065] The temperature at which the weight loss rate of the amide compound is maximized in thermogravimetric analysis (maximum thermal decomposition temperature) may be, for example, 200° C. or higher, or 220° C. or higher, and preferably 250° C. or higher. When the boiling point or thermal decomposition temperature is within the above range, delamination or cracking of the laminate can be suppressed. The upper limit of the boiling point or thermal decomposition temperature is not particularly limited, and may be, for example, 450° C. or lower, 400° C. or lower, or 350° C. or lower.
[0066] The maximum thermal decomposition temperature is a value determined by thermogravimetry (TG) using the following method: A thermal decomposition weight measuring device (NETSCH, STA25000REGULUS) was used to increase the temperature from 20°C to 550°C at a heating rate of 5°C / min in a nitrogen atmosphere, and the weight loss was measured. The temperature at which the differential heat loss was the largest was determined as the maximum thermal decomposition temperature.
[0067] The molecular weight of the amide compound is preferably from 250 to 3000, more preferably from 250 to 1000, and even more preferably from 250 to 500. When the molecular weight of the amide compound is within the above range, the adhesion to the ceramic green sheet (dielectric layer) is further improved.
[0068] The content of the amide compound is preferably 0.01% by mass or more and 1.0% by mass or less based on the entire conductive paste. When the content of the amide compound is within the above range, the adhesion between the dry film and the ceramic green sheet (dielectric layer) is improved. From the viewpoint of further improving the adhesion, the lower limit of the content of the amide compound may be 0.05% by mass or more, or 0.1% by mass or more based on the entire conductive paste. The upper limit of the content of the amide compound may be 0.7% by mass or less, or 0.4% by mass or less.
[0069] The upper limit of the content of the amide compound may be 2% by mass or less, 1.8% by mass or less, 1.5% by mass or less, 1.0% by mass or less, or less than 1.0% by mass. If the content of the amide compound exceeds 1.0% by mass, the adhesion is improved, but when the laminate of the dried film and the ceramic green sheet is subjected to a binder removal treatment, the laminate may be thermally decomposed and gas may be generated. The content of the amide compound may be appropriately adjusted within the above range according to the usage environment, etc.
[0070] The content of the amide compound can be appropriately set according to the type and content of the binder resin. For example, the content of the amide compound may be set according to the content of the butyral resin. For example, the amide compound may be contained in an amount of 10 parts by mass or more and 90 parts by mass or less per 100 parts by mass of the butyral resin. End It may be 60 parts by mass or less, or may be 10 parts by mass or more and 50 parts by mass or less.
[0071] (b) Dispersant When the conductive paste contains a dispersant, the dispersibility of the conductive powder and the ceramic powder can be improved. The dispersant may be, for example, an acid dispersant, a base dispersant, a nonionic dispersant, an amphoteric dispersant, etc., and it is preferable to contain at least one of an acid dispersant and a base dispersant, and it is more preferable to contain an acid dispersant. These dispersants may be used alone or in combination of two or more.
[0072] The acid dispersant may include a carboxylic acid dispersant such as a higher fatty acid, a polycarboxylic acid dispersant, a phosphoric acid dispersant, an acid dispersant having an acidic group such as a polymer surfactant, and the like, and preferably includes at least one of a polycarboxylic acid dispersant and a phosphoric acid dispersant. The polycarboxylic acid dispersant may be a comb-shaped carboxylic acid having a comb structure.
[0073] The higher fatty acid may be an unsaturated carboxylic acid or a saturated carboxylic acid, and is not particularly limited, but examples thereof include stearic acid, oleic acid, myristic acid, palmitic acid, linoleic acid, lauric acid, linolenic acid, and other higher fatty acids having 11 or more carbon atoms. Of these, oleic acid or stearic acid is preferred.
[0074] The acid dispersant may be, for example, oleoyl sarcosine, which is a compound of glycine and oleic acid, or an alkyl monoamine salt type amide compound using a higher fatty acid such as stearic acid or lauric acid instead of oleic acid.
[0075] In addition, from the viewpoint of further improving the effect of suppressing separation between the conductive powder and the ceramic powder, a dicarboxylic acid may be contained. The dicarboxylic acid is a carboxylic acid having two carboxyl groups (COO- groups). The average molecular weight of the dicarboxylic acid is not particularly limited, but is, for example, 200 to 1000. below may be also possible.
[0076] Examples of the basic dispersant include aliphatic amines such as laurylamine, rosinamine, cetylamine, myristylamine, and stearylamine. The conductive paste is a mixture of the above-mentioned acid dispersant and basic dispersant. Agent When the cellulose acylate is contained, the dispersibility may be more excellent and the viscosity stability over time may also be excellent.
[0077] The dispersant is contained in an amount of, for example, 0.01% by mass or more and 3% by mass or less based on the entire conductive paste. The range including the upper limit of the content of the dispersant may be 2% by mass or less, 1% by mass or less, or 0.5% by mass or less. When the content of the dispersant is within the above range, it is possible to improve the dispersibility of the conductive paste and to suppress sheet attack and peeling failure of the green sheet.
[0078] (c) Other additives The conductive paste of the present embodiment may contain other additives in addition to the above components, as necessary. As the other additives, for example, conventionally known additives such as a defoamer, a plasticizer, a surfactant, and a thickener can be used.
[0079] (Conductive paste) The method for producing the conductive paste according to the present embodiment is not particularly limited, and a conventionally known method can be used. The conductive paste can be produced, for example, by stirring and kneading the above-mentioned components with a three-roll mill, a ball mill, a mixer, or the like.
[0080] The conductive paste according to this embodiment contains the above-mentioned amide compound, thereby improving the adhesion between the dry film and the green sheet. One of the reasons for this improved adhesion is thought to be that, as described above, the amide compound inhibits the interaction between resins, thereby moderately softening the dry film (reducing the glass transition temperature Tg) and making it easier to deform.
[0081] For example, when the components other than the conductive powder and ceramic powder in the conductive paste are dried at 120°C for 40 minutes to remove the organic solvent, the glass transition point Tg of the dried body (evaluation sample) is preferably lower than the glass transition point Tg' of a dried body formed under similar conditions except that the amide compound is not included. The amide compound may lower Tg by 10°C or more, 14°C or more, 20°C or more, 25°C or more, or 30°C or more compared to Tg'. For example, the glass transition point Tg of the dried body may be 60°C or less, 55°C or less, or 50°C or less. The lower limit of the glass transition point Tg is, for example, 30°C or more.
[0082] In addition, when the conductive paste contains two or more kinds of resins as binder resins, multiple glass transition points Tg may be measured depending on the resins contained, but the glass transition point Tg of the evaluation sample in this specification indicates the glass transition point Tg in the lowest temperature range. In addition, the glass transition point Tg of the above-mentioned dried body (evaluation sample) can be measured by the method described in the Examples.
[0083] Furthermore, when the conductive paste is applied to the surface of a substrate and dried at 75° C. for 20 minutes to form a dry film, the Vickers hardness of the dry film surface at room temperature is preferably 10 or less, more preferably 9 or less, and even more preferably 8 or less. The lower limit of the Vickers hardness (room temperature) is, for example, 3.5 or more.
[0084] The Vickers hardness of the surface of the dry film at 60° C. is preferably 8 or less, more preferably 7 or less, and even more preferably 6 or less. The lower limit of the Vickers hardness (60° C.) is, for example, 3 or more. When measuring the Vickers hardness (60° C.), it is desirable to condition the dry film to be measured by leaving it at 60° C. for 3 minutes in advance.
[0085] The conductive paste can be suitably used in electronic components such as multilayer ceramic capacitors, and can be particularly suitably used as a paste for internal electrodes of multilayer ceramic capacitors. When the conductive paste is used as a paste for internal electrodes, the viscosity of the conductive paste is 100° C. at a shear rate of 100 (s -1 ) the viscosity can be, for example, about 0.2 Pa·S or more and 30 Pa·S or less.
[0086] [Multilayer ceramic capacitors] Hereinafter, embodiments of the multilayer ceramic capacitor of the present invention will be described with reference to the drawings. In the drawings, the drawings may be represented diagrammatically or at a different scale as appropriate. The positions and directions of the members will be described with reference to an XYZ orthogonal coordinate system shown in FIG. 1 as appropriate. In this XYZ orthogonal coordinate system, the X and Y directions are horizontal directions, and the Z direction is vertical (up-down direction).
[0087] 1A and 1B are diagrams showing a multilayer ceramic capacitor 1. The multilayer ceramic capacitor 1 includes an external electrode 20 and a ceramic laminate 10 in which dielectric layers 12 and internal electrode layers 11 are alternately laminated.
[0088] Hereinafter, a method for manufacturing a multilayer ceramic capacitor using the conductive paste as a paste for internal electrodes will be described. First, the conductive paste is printed on a ceramic green sheet and dried to form a dry film. A plurality of ceramic green sheets having this dry film on the upper surface are laminated by pressure bonding to obtain a laminate, and then the laminate is fired and integrated to produce a ceramic laminate 10 in which internal electrode layers 11 and dielectric layers 12 are alternately laminated. Then, a pair of external electrodes 20 is formed on both ends of the ceramic laminate 10 to manufacture a multilayer ceramic capacitor 1. Hereinafter, a more detailed description will be given.
[0089] First, a green sheet, which is an unfired ceramic sheet, is prepared. For example, the green sheet is prepared by adding a binder resin such as polyvinyl butyral and a solvent such as terpineol to a raw powder of a specific ceramic such as barium titanate, applying the paste for dielectric layer to a support film such as a PET film in a sheet form, and drying to remove the solvent. The thickness of the dielectric layer made of the green sheet is not particularly limited, but is preferably 0.05 μm or more and 3 μm or less from the viewpoint of the demand for miniaturization of the multilayer ceramic capacitor.
[0090] Next, the conductive paste is printed and applied to one side of the green sheet, and then dried to form a dry film on one side of the green sheet, to prepare a plurality of sheets. Note that, from the viewpoint of the requirement for thinning the internal electrode layer 11, it is preferable that the thickness of the dry film formed from the conductive paste is 1 μm or less after drying.
[0091] Next, the green sheet is peeled off from the support film, and the green sheet and the dry film formed on one side thereof are laminated so as to be alternately arranged, and then a laminate is obtained by a heat and pressure treatment. Note that a configuration may be adopted in which protective ceramic green sheets not coated with the conductive paste are further arranged on both sides of the laminate.
[0092] Next, the laminate is cut to a predetermined size to form green chips, and the green chips are subjected to a binder removal treatment and fired in a reducing atmosphere to produce a laminated ceramic fired body (ceramic laminate 10). The binder removal treatment is preferably performed in air or N2 gas atmosphere. The temperature during the binder removal treatment is, for example, 200°C or higher and 400°C or lower. The temperature is preferably held for 0.5 hours or higher and 24 hours or lower during the binder removal treatment. The firing is performed in a reducing atmosphere to suppress oxidation of the metal used in the internal electrode layer, and the temperature during firing of the laminate is, for example, 1000°C or higher and 1350°C or lower, and the temperature is held for, for example, 0.5 hours or higher and 8 hours or lower.
[0093] By firing the green chip, the organic binder in the ceramic green sheet is completely removed, and the ceramic raw material powder is fired to form the ceramic dielectric layer 12. The organic vehicle in the dry film is also removed, and the nickel powder or the alloy powder mainly composed of nickel is sintered or melted and integrated to form the internal electrode layer 11, forming a multilayer ceramic sintered body in which a plurality of dielectric layers 12 and internal electrode layers 11 are alternately stacked. Note that, from the viewpoint of taking oxygen into the dielectric layer to increase reliability and suppressing reoxidation of the internal electrodes, the sintered multilayer ceramic sintered body may be subjected to an annealing treatment.
[0094] A pair of external electrodes 20 is then provided on the produced fired laminated ceramic body to manufacture the laminated ceramic capacitor 1. For example, the external electrode 20 includes an external electrode layer 21 and a plating layer 22. The external electrode layer 21 is electrically connected to the internal electrode layer 11. Note that, for example, copper, nickel, or an alloy thereof can be suitably used as the material for the external electrode 20. Note that, as the electronic component, electronic components other than the laminated ceramic capacitor can also be used. EXAMPLES
[0095] The present invention will be described in detail below based on examples and comparative examples, but the present invention is not limited to these examples.
[0096] [Evaluation method] (Adhesion evaluation) A conductive paste (sample) was applied to the surface of a green sheet containing barium titanate and polyvinyl butyral that had been prepared in advance, forming a conductive paste film with a wet film thickness of 35 μm. The resulting green sheet and the sheet consisting of the conductive paste film for the internal electrodes formed on the surface were dried at 75°C for 20 minutes to form a dry film on the green sheet. The dried sheet (dried film-green sheet) and another green sheet were stacked in such a way that the surface coated with the conductive paste was sandwiched between the green sheets, and then pressed at a temperature of 40°C and a pressure of 20 MPa for 20 seconds to create a laminate (for evaluation).
[0097] The obtained laminate was cut into 1 cm squares, and then both sides of the laminate were set on the jigs of a tensile tester (Shimadzu Corporation, AGS-50NX) using tape, and a tensile test was then performed. The breaking force (the force to peel the dry film from the green sheet) was recorded at a test speed of 20 mm / min. The breaking force of Comparative Example 1 was set as 100%, and each breaking force was evaluated in %.
[0098] (hardness measurement) The surface (dried film side) of the green sheet on which the conductive paste film (dried film) was formed under the same conditions as those for the adhesion evaluation was measured for Vickers hardness at n=5 points under a test force of 98 mN using a micro Vickers hardness tester (Shimadzu Corporation, HMV-G21DT), and the average value was calculated. The hardness measurement was performed by attaching a sample to a glass substrate and placing it on a heating stage, which is the sample stand of the hardness tester, at room temperature (25°C) without heating and at a heated state of 60°C. When measuring the Vickers hardness (60°C), the dried film to be measured was left at 60°C for 3 minutes to condition it, and then the measurement was performed while it was heated at 60°C.
[0099] (Measurement of glass transition temperature Tg) The components contained in the conductive paste, excluding the conductive powder and ceramic powder, i.e., ethyl cellulose resin, polyvinyl butyral resin, additives, and organic solvent, were weighed out in the same amounts as those contained in the conductive paste, and mixed for 4 minutes at 2000 rpm using a planetary mixer (Thinky, ARE-310), and the resulting liquid (mixture) was applied to a PET film with a wet film thickness of 254 μm using an applicator, and dried at 120°C for 40 minutes to obtain a sample for evaluation. The organic solvent in the mixture was removed during drying.
[0100] Using a differential scanning calorimeter (Netsch Japan, DSC3100), 10 mg of the dried sample for evaluation was placed in an aluminum pan and heated from 0°C to 140°C at a heating rate of 10°C / min under a nitrogen flow of 100 mL / min. The glass transition temperature Tg on the low temperature side was determined from the peak of the endothermic curve obtained by heating from 0°C to 140°C at a heating rate of 10°C / min.
[0101] (pyrolysis temperature measurement) The thermal decomposition temperature of the additives used in the conductive paste was measured using a thermal decomposition weight measuring device (NETSCH, STA25000REGULUS). The measurement temperature was measured in a nitrogen atmosphere from 20°C to 550°C at a heating rate of 5°C / min. The temperature at which the differential heat loss was the largest, i.e., the temperature at which the weight loss rate in thermogravimetric analysis was the largest, was taken as the thermal decomposition temperature (maximum thermal decomposition temperature).
[0102] [Materials used] (conductive powder) As the conductive powder, Ni powder (SEM average particle size: 0.2 μm) was used.
[0103] (ceramic powder) Barium titanate (BaTiO3; SEM average particle size 0.10 μm) was used as the ceramic powder.
[0104] (binder resin) As the binder resin, polyvinyl butyral resin (PVB) and ethyl cellulose resin (EC) were used.
[0105] (Dispersant) In both the examples and the comparative examples, a polycarboxylic acid-based dispersant, which is an acid-based dispersant, was used as the dispersant (additive) contained in common.
[0106] (Additives) As the amide compounds, the following compounds (4) (compound of the above structural formula (2)) and (5) (compound of the above structural formula (3)) were used.
[0107] [ka]
[0108] [ka]
[0109] As comparative examples, the following additives were used. Additive a: Polycarboxylic acid having polyoxyalkylene as a graft chain Additive B: Oxyethylene laurylamine (polyetheramine) Additive C: Dicarboxylic acid
[0110] (Organic solvent) The organic solvents used were dihydroterpineol (DHT) and mineral spirits (MSA).
[0111] [Example 1] Conductive powder 49 mass%, ceramic powder 12 mass%, acid dispersant 0.15 mass%, additive of formula (4) 0.3 mass%, binder resin 2.5 mass% (PVB:EC=7:3 (mass ratio)), and organic solvent (DHT:MSA=60:40 (mass ratio)) as the remainder were added to make a total of 100 mass%, and these materials were mixed to prepare a conductive paste. The content of each material in the conductive paste and the evaluation results are shown in Table 1.
[0112] [Examples 2 to 5, Comparative Examples 1 to 4] A conductive paste was prepared and evaluated in the same manner as in Example 1, except that the type and content of the additives were changed as shown in Table 1. The content of each material in the conductive paste and the evaluation results are shown in Table 1.
[0113] [Table 1]
[0114] (Evaluation Results) The conductive pastes of Examples 1 to 5 had a lower glass transition point (Tg) in the low temperature range, a lower Vickers hardness, and improved adhesion, compared to the conductive pastes of Comparative Examples 1 to 4, which did not contain the amide compound represented by formula (1) or (2). [Industrial Applicability]
[0115] When the conductive paste of the present invention is used to form an internal electrode of a multilayer ceramic capacitor, a highly reliable multilayer ceramic capacitor can be obtained with high productivity. Therefore, the conductive paste of the present invention can be suitably used for the internal electrodes of multilayer ceramic capacitors, which are chip components of electronic devices such as mobile phones and digital devices that are becoming increasingly smaller.
[0116] The technical scope of the present invention is not limited to the aspects described in the above embodiments. One or more of the requirements described in the above embodiments may be omitted. The requirements described in the above embodiments may be combined as appropriate. In addition, to the extent permitted by law, the disclosures of all documents cited in the above embodiments are incorporated as part of the description in this text. In addition, to the extent permitted by law, the contents of Japanese Patent Application No. 2022-052666 are incorporated as part of the description in this text.
[0117] The embodiment of the present invention may include the following features.
[0118] [1] A conductive paste containing a conductive powder, an additive, a binder resin and an organic solvent, The additive includes a compound having a structural portion represented by the following formula (1): Conductive paste. [ka] (However, R 1 represents a saturated or unsaturated aliphatic hydrocarbon group having 8 to 25 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH-) substituted with oxygen (-O-); R 2 represents hydrogen or a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH2-) substituted with oxygen (-O-).
[0119] [2] The conductive paste according to [1], wherein the compound has a structure represented by the following formula (2) or the following formula (3). [ka] [ka] (However, R 1 , R 5 each independently represents a saturated or unsaturated aliphatic hydrocarbon group having 8 to 25 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH-) substituted with oxygen (-O-); R 2 , R 3 , R 4 each independently represents a hydrogen atom or a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and one or more methylenes (-CH-) in the aliphatic hydrocarbon group may be substituted with oxygen (-O-); R 6represents a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group may have one or more methylenes (-CH2-) substituted with oxygen (-O-).
[0120] [3] The conductive paste according to [1] or [2], wherein the compound is contained in an amount of 0.01 mass % or more and 2.0 mass % or less with respect to the entire conductive paste.
[0121] [4] The conductive paste according to any one of [1] to [3], wherein the compound has a temperature at which a weight loss rate becomes maximum in a thermogravimetric analysis of 200° C. or higher.
[0122] [5] The conductive paste according to any one of [1] to [4], wherein the compound has a molecular weight of 250 or more and 3,000 or less.
[0123] [6] The conductive paste according to any one of [1] to [5], further comprising an acidic dispersant and / or a basic dispersant.
[0124] [7] The conductive paste according to any one of [1] to [6], wherein the conductive powder contains at least one metal powder selected from Ni, Pd, Pt, Au, Ag, Cu, and alloys thereof.
[0125] [8] The conductive paste according to any one of [1] to [7], wherein the conductive powder has an average particle size of 0.05 μm or more and 1.0 μm or less.
[0126] [9] The conductive paste according to any one of [1] to [8], wherein the binder resin contains a butyral resin.
[0127]
[10] The conductive paste according to any one of [1] to [9], further comprising a ceramic powder.
[0128]
[11] The conductive paste according to
[10] , wherein the ceramic powder contains barium titanate.
[0129]
[12] The conductive paste according to
[10] or
[11] , wherein the ceramic powder has an average particle size of 0.01 μm or more and 0.5 μm or less.
[0130]
[13] The conductive paste according to any one of
[10] to
[12] , wherein the ceramic powder is contained in an amount of 1 mass % or more and 20 mass % or less with respect to the entire conductive paste.
[0131]
[14] The conductive paste according to any one of [1] to
[13] , which is for use in an internal electrode of a multilayer ceramic component.
[0132]
[15] An electronic component formed by using the conductive paste according to any one of [1] to
[14] .
[0133]
[16] At least a laminate in which a dielectric layer and an internal electrode layer are laminated, The internal electrode layers are formed using the conductive paste according to
[14] . [Explanation of symbols]
[0134] 1. Multilayer ceramic capacitors 10 Ceramic laminate 11 Internal electrode layer 12 Dielectric layer 20 External electrode 21 External electrode layer 22 Plating layer
Claims
1. A conductive paste comprising a conductive powder, an additive, a binder resin and an organic solvent, The additive includes a compound having a structural portion represented by the following formula (1): Conductive paste. 【Chemistry 1】 (However, R 1 represents a saturated or unsaturated aliphatic hydrocarbon group having 8 to 25 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group contains one or more methylene (-CH 2 -) may be replaced by oxygen (-O-), R 2 represents hydrogen or a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group contains one or more methylene (-CH 2 -) may be replaced with oxygen (-O-).
2. The conductive paste according to claim 1 , wherein the compound has a structure represented by the following formula (2) or the following formula (3): 【Chemistry 2】 【Chemistry 3】 (However, R 1 , R 5 each independently represents a saturated or unsaturated aliphatic hydrocarbon group having 8 to 25 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group contains one or more methylene (-CH 2 -) may be replaced by oxygen (-O-); R 2 , R 3 , R 4 each independently represents hydrogen or a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group contains one or more methylene (-CH 2 -) may be replaced by oxygen (-O-); R 6 represents a saturated or unsaturated aliphatic hydrocarbon group having 1 to 6 carbon atoms, the aliphatic hydrocarbon group may be linear or branched, and the aliphatic hydrocarbon group contains one or more methylene (-CH 2 -) may be replaced with oxygen (-O-).
3. The conductive paste according to claim 1 , wherein the compound is contained in an amount of 0.01% by mass or more and 2.0% by mass or less based on the entire conductive paste.
4. The conductive paste according to claim 1 , wherein the compound has a temperature of 200° C. or higher at which a weight loss rate becomes maximum in a thermogravimetric analysis.
5. 2. The conductive paste according to claim 1, wherein the molecular weight of the compound is 250 or more and 3,000 or less.
6. The conductive paste according to claim 1 , further comprising an acidic dispersant and / or a basic dispersant.
7. The conductive paste according to claim 1 , wherein the conductive powder contains at least one metal powder selected from the group consisting of Ni, Pd, Pt, Au, Ag, Cu, and alloys thereof.
8. The conductive paste according to claim 1 , wherein the conductive powder has an average particle size of 0.05 μm or more and 1.0 μm or less.
9. The conductive paste according to claim 1 , wherein the binder resin comprises a butyral resin.
10. The conductive paste of claim 1 , further comprising a ceramic powder.
11. The conductive paste of claim 10 , wherein the ceramic powder comprises barium titanate.
12. The conductive paste according to claim 10 , wherein the ceramic powder has an average particle size of 0.01 μm or more and 0.5 μm or less.
13. The conductive paste according to claim 10 , wherein the ceramic powder is contained in an amount of 1% by mass to 20% by mass based on the entire conductive paste.
14. The conductive paste according to claim 1, which is used for internal electrodes of multilayer ceramic parts.
15. An electronic component formed by using the conductive paste according to any one of claims 1 to 14.
16. The laminate has at least a dielectric layer and an internal electrode layer stacked thereon, A multilayer ceramic capacitor, wherein the internal electrode layers are formed using the conductive paste according to claim 14.
Citation Information
Patent Citations
Conductive paste and method for producing the same
JP2017135058A
Conductive metal powder paste
JP2017183247A
Paste for internal electrodes, method for manufacturing the same, and multilayer ceramic capacitor
JP2018037630A
Conductive paste
JP2018055933A
Conductive paste, dried film thereof, internal electrode arranged by baking the same, and multilayer ceramic capacitor having the internal electrodes
JP2019121744A